The Influence of Integrated Pest Management Principles on the Efficiency of Rice Farming in Anjatan Utara Village - Faisal Aulia Meidiyanto; Abdul Rohman; Dony Nurisman; Akhmad Jaeroni; Dwi Purnomo (Journal Of Social Science (JoSS), 2025)
This study analyzes the influence of the principle of Integrated Pest Control (PHT) on the efficiency of rice farming in North Anjatan Village, Indramayu Regency. PHT is an approach to managing Plant Pest Organisms (OPT) by considering technical, economic, ecological, and social aspects. The research method used was quantitative descriptive with data collection through questionnaires to 96 rice farmers. The data were analyzed using multiple linear regression to test the influence of the variables of Healthy Plant Cultivation (X1), Natural Enemy Utilization (X2), Routine Observation (X3), and Pest Risk Management (X4) on the Efficiency of Rice Farming (Y). The results showed that the Utilization of Natural Enemies and Pest Risk Management had a significant effect on the efficiency of farming, while Healthy Plant Cultivation and Routine Observation did not have a significant influence. Simultaneously, these four variables affect the efficiency of farming with an F value of 22.409 and a significance of 0.000. The determination coefficient (R²) of 49.6% shows that the independent variable explains almost half of the variation in rice farming efficiency. In conclusion, the application of PHT through the use of natural enemies and pest risk management is effective in improving the efficiency of farming. It is recommended that farmers focus more on this aspect, while the government and academics can provide further training to optimize the implementation of PHT.